Social entrepreneurship - KOÇOĞLU SAZKAYA, MERVE (IU Press, 2023)
Although the dilution of borders with globalization brings many conveniences for humanity, it also causes problems. Now the problem of one nation living in a different part of the world becomes the problem of all humanity. Some of these global problems are the rapid consumption of natural resources, global warming, hunger, lack of access to water, and war. Over time, the state has proven insufficient to solve these problems. For this reason, various non-governmental organizations have been established on the global and local scales. These organizations have started to struggle with the common problems of humanity as well as their own countries. Eventually, just like states, these organizations too remained inadequate. On the other hand, large corporations some with budgets bigger than that of many states have almost started to rule the world. These businesses initially focused only on generating commercial income. However, they have increasingly faced pressure from society to generate solutions to humanity’s increasing problems today. Therefore, they have started to produce solutions to social problems through commercial gain. In the literature, this situation is termed social entrepreneurship. Social entrepreneurship refers to the activities businesses carry out in order to use the factors of production to find solutions to social problems and provide social benefits. In this context, social entrepreneurship is seen as the building block of social development, and this concept is increasingly attracting the attention of both academics and the business world. Therefore, in this part of the book, the definition of social entrepreneurship and social entrepreneur concepts, the difference between social entrepreneurship and entrepreneurship, terms related to social entrepreneurship, and the importance of social entrepreneurship will be discussed, and examples of social entrepreneurship will be shared.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)